Pendampingan Kader Dalam Pemberian Edukasi Latihan Fisik Berbasis Self Care Pada Pasien Dan Keluarga Pasien DM Tipe 2 - Yasa, I Dewa Putu Gede Putra; Rasdini, I Gusti Ayu Ari; Rahayu, V.M. Endang Sri Purwadmi (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2023)
Background: Type 2 diabetes mellitus can affect all aspects of the patient's life so that it can be life threatening if not treated properly. The problems experienced by Type 2 Diabetes Mellitus patients can be minimized by having sufficient knowledge and ability to control their disease with self-care. Self Care describes patient behavior carried out consciously and independently with the aim of optimizing and increasing independence in terms of health. Development of an empowerment program for Type 2 Diabetes Mellitus patients through a cadre approach. Purpose: the aim of this activity is to increase cadres' ability to manage self-care for type 2 diabetes mellitus patients. Method: The method of community service activities is cadre empowerment. Activities were carried out in Sembung Village, Mengwi, Badung with 50 health cadres as partners. Result: The result of this activity is that there has been an increase in understanding by 60% and cadres have increased the ability of type 2 Diabetes Mellitus patients to carry out independent care. Conclusion: The conclusion is that health cadres are able to act as motivators and mentors in carrying out comprehensive self-care for Type 2 Diabetes Mellitus patients.